Patients' experiences of assessment and detention under mental health legislation: systematic review and qualitative meta-synthesis. Issue 3 (May 2019) - Akther, Syeda Ferhana; Molyneaux, Emma; Stuart, Ruth; Johnson, Sonia; Simpson, Alan; Oram, Sian
Abstract : Background: Understanding patient experiences of detention under mental health legislation is crucial to efforts to reform policy and practice. Aims: To synthesise qualitative evidence on patients' experiences of assessment and detention under mental health legislation. Method: Five bibliographic databases were searched, supplemented by reference list screening and citation tracking. Studies were included if they reported on patient experiences of assessment or detention under mental health legislation; reported on patients aged 18 years or older; collected data using qualitative methods; and were reported in peer-reviewed journals. Findings were analysed and synthesised using thematic synthesis. Results: The review included 56 papers. Themes were generally consistent across studies and related to information and involvement in care, the environment and relationships with staff, as well as the impact of detention on feelings of self-worth and emotional state. The emotional impact of detention and views of its appropriateness varied, but a frequent theme was fear and distress during detention, including in relation to the use of force and restraint. Where staff were perceived as striving to form caring and collaborative relationships with patients despite the coercive nature of treatment, and when clear information was delivered, the negative impact of involuntary care seemed to be reduced. Conclusions: Findings suggest that involuntary in-patient care is often frightening and distressing, but certain factors were identified that can help reduce negative experiences. Coproduction models may be fruitful in developing new ways of working on in-patient wards that provide more voice to patients and staff, and physical and social environments that are more conducive to recovery. Declaration of interest: None.